Analysis of frequency and severity of relapses in multiple sclerosis patients treated with cladribine tablets or placebo: The CLARITY and CLARITY Extension studies. (January 2022) - De Stefano, Nicola; Sormani, Maria Pia; Giovannoni, Gavin; Rammohan, Kottil; Leist, Thomas; Coyle, Patricia K; Dangond, Fernando; Keller, Birgit; Alexandri, Nektaria; Galazka, Andrew
Background: In the CLARITY (CLAdRIbine Tablets treating multiple sclerosis orallY) study of patients with relapsing-remitting multiple sclerosis, treatment with cladribine tablets 3.5 mg/kg (CladT) significantly reduced the annualised relapse rate (ARR) versus placebo; this effect was sustained in CLARITY Extension, without further treatment. Objective: To assess the frequency and severity of relapses in patients treated with CladT versus placebo in CLARITY over 2 years and evaluate the durability of effect in patients who received no further treatment for 2 years in CLARITY Extension. Methods: In this post hoc analysis, ARRs were calculated for qualifying and all relapses, and qualifying and all severe relapses (i.e. requiring steroid treatment or leading to hospitalisation) in patients treated with CladT ( n  = 433) and placebo ( n  = 437) in CLARITY, and those from the CladT group who received placebo in CLARITY Extension ( n  = 98). Results: At Month 6, Year 1 and Year 2, patients receiving CladT had a significantly lower risk of qualifying or all relapses (all p  < 0.0001), and qualifying or all severe relapses (all p  < 0.005), compared with placebo. This effect was sustained in CLARITY Extension without further treatment. Conclusion: The results show durable efficacy of cladribine tablets 3.5 mg/kg for reducing frequency and severity of relapses in patients with relapsing-remitting multiple sclerosis. CLARITY: NCT00213135; CLARITY Extension: NCT00641537